Study of the yeast cytosolic Hsp70-system in protein homeostasis and life span regulation - The molecular chaperone GFP-Hsp104 before and after heat stress in a Hsp70-mutant yeast strain with exogenous complementation of wildtype and chimaeric mutant alleles of yeast Hsp70-alleles - Andersson, Rebecca; Hanzén, Sarah; Vielfort, Katarina; Nyström, Thomas (University of Gothenburg, 2020)
Our study aims to answer the question "Which functions of the Hsp70 class of molecular chaperones are essential for yeast to maintain a standard replicative life span?". To answer this question, we utilised the disparate functions of the Hsp70's Ssa1 and 2 and their paralog Ssa4 in a yeast strain that lacks Ssa1/2 but has an ectopically increased production of Ssa4. We have gathered data on the behaviour of several different markers for protein aggregation under different circumstances, as well as data on proteins from other classes of molecular chaperones. The bulk of the data is in the form of multichannel microscopy images from widefield microscopy, with a few sets of western blots of protein extracts.

Fluorescence microscopy of live yeast cells at mid-exponential growth and after 30 minutes of heat shock. The cells were grown in complete synthetic media lacking histidine and leucine with 2 % galactose as carbon source. All strains carry two plasmids; one expressing GFP-HSP104 under the control of the GAL-promoter and one expressing SSA1, SSA4 or SSA1/SSA4 chimaeras (alternatively an empty plasmid) under the control of the GPD-promoter.
The dataset was collected through fluorescence microscopy.
The image files are provided in Carl Zeiss Image format (.czi).

Vi har systematiskt studerat vilka funktioner hos de cytosoliska molekylära chaperonerna av klassen Hsp70 hos jäst som krävs för att upprätthålla en normal livslängd.

Fluorescensmikroskopi av levande jäst i mitten av den exponentiella tillväxtfasen före och efter 30 minuter värmestress. Jästen är odlad i syntetiskt medium utan histidin och leucin med 2 % galaktos som kolkälla. Alla avbildade stammar bär på två plasmider; en som uttrycker GFP-HSP104 under kontroll av en GAL-promotor samt en som uttrycker SSA1, SSA4 eller SSA1/SSA4 chimärer (alternativt en tom plasmid) under kontroll av en GPD-promotor.
Datasetet har samlats in genom fluorescensmikroskopi.
Bildfilerna är i Carl Zeiss Image-format (.czi).
Studier av det cytosoliska Hsp70-systemet från jäst och dess roll i proteinhomeostas och reglering av livslängd - Det molekylära chaperonet GFP-Hsp104 avbildat före och efter värmestress i Hsp70-mutanta jäststammar som komplementerats med exogena vildtyp- och chimärmutanta Hsp70-alleler
Keywords: Cellular Senescence; Cellåldrande; Molecular Chaperones; Molekylära chaperoner; HSP70 Heat-Shock Proteins; HSP70-värmechockproteiner; Proteostasis Deficiencies; Proteostasbrist; Cell Biology; Cellbiologi; Microbiology; Mikrobiologi; Cell and Molecular Biology; Cell- och molekylärbiologi; Molecular Biology; Molekylärbiologi